Holguín Zamorano, Germán. La Guerra contra los Medicamentos Genéricos: Un crimen silencioso. Editorial Aguilar, Bogotá, 2014, ISBN: 978-958-758-763-0, 328 p. - Tapias Gutiérrez, Agustín Asier; Unicolombo (2017)
null